A construção dos números reais e aplicações - Silva, José Elias da (2016)
In this study we work two constructions of the real numbers system. The construction the system of real numbers by cuts or straight sections in the set of rational numbers, advanced by Dedekind, and the construction of the real number as equivalence class of fundamental sequences of rational numbers, idea introducel by Cantor. Related to this approach, we dedicate a Chapter to show density of the rational num- bers and irrational numbers in the set of real numbers. Later, in a more synthesized form than the above constructions,we present other ap- proachs which the fundamental idea of real numbers is more clear. Finally we use method axiomatic in order to show the uniqueness of the real numbers system, thus, we conclude that there is a complete and orderly body which is unique up to isomorphism . This unique body is named the real numbers body.